Instagram Sebagai Media Komunikasi Pemasaran Hijab Syar’i Azmah Muslimah - Isna Siskawati; Indri Yuliani (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2021)
Marketing communication is an important part in marketing products. It takes planning, strategy and selection of the right marketing media to be able to achieve the desired marketing goals. By utilizing current technology as a marketing medium, it is expected to increase sales volume. Instagram is an option that can be used as a marketing communication medium, plays a role in increasing sales volume and expanding the company's market segmentation by utilizing various features contained in it. This study aims to determine the role of social media Instagram as a marketing communication medium for Azmah Muslimah. This study uses a marketing communication approach with qualitative descriptive research. Data were analyzed inductively from the results of interviews, observations, and documentation. The results of this study indicate that Azmah Muslimah in marketing her products, uses the features on Instagram, such as uploading photos, captions, arroba, hashtags, instastory, and highlights. In addition to utilizing the Instagram features, Azmah Muslimah also uses modeling services for each photo of her products and endorses celebrities (instagram celebrities) and provides giveaways to support product marketing. Azmah Muslimah also implements a triangular marketing strategy, namely the STP Marketing Strategy (Segmentation, Targeting, Positioning), the 4P marketing mix (Product, Price, Place, Promotion), and the customer oriented 4C (customer solution, customer cost, convenience, communication).